Antigen specificities and functional properties of MR1-restricted T cells. (February 2021) - De Libero, Gennaro; Chancellor, Andrew; Mori, Lucia
Highlights: MR1, a non-polymorphic ubiquitous antigen presenting molecule presents small metabolites to T cells. MR1T cells recognize small drugs and microbial metabolites presented by MR1. MR1T cells also recognize self-metabolites accumulating in tumor cells. MR1T cells are multi-functional and express polyclonal TCR heterodimers. Abstract: MR1 is an MHC class I-like molecule with unique structural and biological features that make it an important member among the molecules involved in antigen presentation to T cells. Distinctive features include ubiquitous expression of the MR1 gene and its monomorphism. Another relevant property is that the MR1 protein appears at very low levels on the plasma membrane and its surface expression is regulated by antigen binding. Finally, the nature of presented antigens differs from those that bind other presenting molecules and includes small metabolites of microbial and self-origin, small drugs and tumor-associated antigens. This opinion paper describes in detail some of those features and discusses recent literature in the field.